2020
DOI: 10.1364/ol.389309
|View full text |Cite
|
Sign up to set email alerts
|

On the measurement of the nonlinear optical response of graphene dispersions using fs lasers

Abstract: In this work, the nonlinear optical (NLO) response of some graphene dispersions is investigated under low (i.e., 10 Hz) and high (i.e., 80 MHz) repetition rate femtosecond (fs) laser excitation conditions, using Z -scan, optical Kerr effect (OKE), and a combination of Z -scan and thermal lensing techniques. It is shown, that the NLO response of graphene dispersions is negligible under low repetition rate fs laser excitation, while it becomes very large under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The nonlinear refractive index obtained using an excitation wavelength at 1150 nm is of the same order of magnitude with our reported values for the Sb 2 Te 3 layers. It has to be noted that the negative nonlinear refraction obtained here (self-defocusing) is in accordance with several previous experimental and theoretical studies on graphene systems. A negative nonlinear refraction has been also presented in ref in the case of another 2D material, black phosphorus, while the nonlinear refraction is 6–7 orders of magnitude lower than that reported in this work.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The nonlinear refractive index obtained using an excitation wavelength at 1150 nm is of the same order of magnitude with our reported values for the Sb 2 Te 3 layers. It has to be noted that the negative nonlinear refraction obtained here (self-defocusing) is in accordance with several previous experimental and theoretical studies on graphene systems. A negative nonlinear refraction has been also presented in ref in the case of another 2D material, black phosphorus, while the nonlinear refraction is 6–7 orders of magnitude lower than that reported in this work.…”
Section: Resultssupporting
confidence: 92%
“…In another work similar values have been found (10 −7 ∼ 10 −6 esu) by employing the same repetition rate. 39 Very recently Karampitsos et al 40 have investigated graphene dispersions and have demonstrated that the repetition rate of the laser plays a very important role on the NLO response of graphene. Using a high repetition rate (i.e., 80 MHz) they have shown that thermal effects dominate the nonlinearities.…”
Section: Acs Appliedmentioning
confidence: 99%
“…Indeed, it has been previously reported that the optical nonlinearities of graphene layers were strongly depending on the employed repetition rate. 11 We estimate that at 100 Hz thermal effects are negligible. Several zones of each sample were scanned during this study to prove that a homogeneous optical nonlinearity was present all over the surface of the samples.…”
Section: Z-scan Resultsmentioning
confidence: 85%
“…In addition, it needs to be emphasized that although the relatively low absorption of ZnO samples at 1064 nm can minimize the possibility of the contribution of thermal effects, the conversion of the absorbed energy into phonons from non-radiative absorption processes may not be negligible, when excitation occurs under high-repetition rate laser sources with the nano-second pulse width regime. Actually, the Gaussian laser beams during their long-term interactions with ZnO samples can be partially adsorbed and then converted to heat to form a lens-like optical element due to cumulative thermal effects [72].…”
Section: Discussionmentioning
confidence: 99%